Pengembangan Media Pembelajaran Matematika Sekolah Dasar Berbasis Macromedia Flash - Ikmallul Hidayah; Sofia Edriati; Ami Anggraini Samudra (Horizon, 2022)
In the mathematics learning materials taught by teachers of SDN 14 Kampung Jambak still using lecture methods anduse of learning media in schools have never been applied in the learning process. The research aims to produce a valid and practical Macromedia Flash-based learning medium on math subjects. This research uses the MDLC (Multimedia Development Life Cycle) development model. The population in this study is students and students of class V SDN 14 Kampung Jambak which amounted to 53 people. Sampling techniques use random sampling techniques, which number 13students, data collection instruments in the form of validation sheets and practical questionnaires. Data analysis uses percentage techniques. Assessment results from media experts with an average of 92.55% of categories are very valid, and assessments from material experts with an average of 91.66% of categories are very valid. The results of practicality tests by teachers with a percentage of 92.66% so that it is declared very practical, and practical results from students with an average of 91.14% are declared very practical. So it can be concluded that macromedia flash-based learning media is very valid and very practical to use as an alternative medium in the learning process.